Food Security, Right to Food, Ethics of Sustainability Legal, Economic and Social Policies Authors - Califano, Licia (Diritto, 2023)
Food security, understood in its broadest sense as the 'right to food', is a fundamental right preordained to respect for life itself. No human being can be guaranteed the right to life if, at the same time, the need for qualitatively and quantitatively sufficient food is not respected. This is a value of food which, in the integrated and interdisciplinary methodological perspective embraced in this book, combines the existential dimension of food with reasoning oriented towards elaborating political choices of intervention. This approach highlights the limits of a socio-economic model that continues to move within a paradigm far removed from the logic of sustainable consumption and respect for fundamental rights.